Teachers' vulnerability. Thoughts of a teacher and his evaluation process after a morning with Neus Sanmartí - Felip Lorenzo (Universitat Autònoma de Barcelona, 2020)
When most teachers start to create a learning proposal, we usually focus on activities, contents or competences that we want to work on, but the main problem is that we tend to leave the assessment to the end. In our Summer School, we made the same mistake. One of the things we have learned from feminism is to share our vulnerability and build from it. Our vulnerability as a group is that we teachers find assessing hard. Willing to improve this, we invited Neus Sanmartí at the EEE19. Since then, we have gone through a deep assessment process and we have learned more about ourselves than we expected. In this article we share our learning process and our assessment about what we know about assessment and learning.